Association Between Parental Parenting Style Disparities and Mental Health: An Evidence From Chinese Medical College Students - Ding, Gan; Xu, Lingzhong; Sun, Long (Frontiers in Public Health, 2022)
Background: The associations between parental parenting styles and adolescents’ development and health problems were also identified in a series of studies. However, the interactive impact of mother’s and father’s parenting style was less reported, which was implied in previous studies. In this study, we aim to analyze the associations between parental parenting style disparities and mental health among medical college students. Method: A cross-sectional study was conducted among medical college students in Shandong province, China, and 2598 medical college students with parents were analyzed in this study. Items in a short form of EMBU was used to calculate the parental parenting style disparities. Mental health was evaluated by the Kessler 10 scale. Results: The results of linear regressions showed that parental nurture rejects disparities (RD, β=0.50, p<0.001), parental emotional warmth disparities (WD, β=0.33, p<0.001), parental overprotective disparities (OD, β=0.25, p<0.001), and total disparities in parenting styles (TD, β=0.15, p<0.001) were associated with mental health among medical college students, respectively. The other associated factors were age, ethnicity, chronic disease, above average family economic status, and good parental relationship. Conclusions: Our findings supported the positively association between parental parenting style disparities and mental health problems. Further studies can test the mechanism and intervention of the findings about the importance of parental parenting style consistence on mental health.